Detecting financial statement fraud through new fraud diamond model: the case of Indonesia. Issue 3 (26th July 2021) - Khamainy, Arief Hidayatullah; Ali, Mahrus; Setiawan, M. Arif
Abstract : Purpose: The purpose of this paper is to evaluate the effect of the new fraud diamond model in explaining financial statement fraud. Design/methodology/approach: The variables used to examine the factors consist of motivation, opportunity, personal integrity and capability. This research used manufactured companies listed in the Indonesia Stock Exchange of the 2015–2019 period as the population. Findings: There has been a positive influence between personal financial need (OSHIP), nature of the industry (RECEIVABLE) and history of sale (SG) toward financial statement fraud, while the negative effect is found only in the effective monitoring (IND). Research limitations/implications: The new fraud diamond model theory which is used as a reference in this study is a new and under-developed theory. So the author suggests that further research on this theory be carried out to strengthen the new fraud diamond model theory and ensure whether it can be used as a reference to find out the causes of financial statement fraud. In addition, the object used in this study is limited to manufacturing companies, so the author suggests that further research combine several types of companies. Originality/value: The research finding supports the new fraud diamond model theory in elaborating the financial statement fraud phenomenon.